Performance analysis and evaluation of a hybrid erasure error correction scheme in wireless real-time multicast systems - Guo-ping TAN; Li-zhong XU; Xi-jun YAN; Zai-jun HUA (Tongxin xuebao)
In order to analyze and evaluate accurately the performance of erasure error correction (EEC) schemes in wireless real-time multicast (WRM) systems,A method which relying on the Gilbert-Elliot (GE) channel model and the practical experimental data was proposed.Namely,a closed-form expression for analyzing the performance of a hybrid EEC scheme over GE channel was contributed.Then,a validating and evaluating system w th real-time multicast services over WLAN was designed.Based on the system,the maximum likelihood estimation method was adopted for statistical evaluations.The results show that the GE model can match the practical erasure error channel accurately.Both the analysis results of the hybrid EEC scheme and the experimental lts are basically coincident,which validates the accuracy of the method.This method is of reference significance for analyzing and evaluating accurately all kinds of EEC schemes in WRM systems.